Personnel economics: An economic approach to human resource management - Uschi Backes-Gellner (Management Revue, 2004)
The theoretical idea of personnel economics is to apply simple economic principles to the field of human resources management. Personnel economics as a research field has grown rapidly since the first text book on 'Personnel Economics' was published in 1998. The development is driven by new theoretical insights based on institutional and behavioural economics and new empirical methods and data sets. Those new theoretical insights are very fruitful to analyze reasons and consequences of various human resource management practices, to understand what actually drives and motivates employees, and what causes organisations to be successful or to fail. With the new data sets and econometric methods the theories that have been laid out in personnel economics either many years ago or very recently can now be tested thoroughly. And the evidence produced by the new data and methods is strongly supportive, which is not only reassuring for researchers, but it also suggests that practitioners can actually rely on the ideas because they are born out in the data. So, personnel economics is not only a vivid research field, but also of great value for human resource managers, particularly for those taking strategic HR decisions. The fruitfulness of personnel economics is demonstrated with four examples: training strategies of companies, recruiting in tight labour markets, career incentives, team size and effort, and entrepreneurial signalling towards employees and creditors.
Keywords: 650; personnel economics; strategic human resource management; training strategies; hiring; career uncentives; effort in teams; entrepreneurial signalling; Personalmanagement; Strategisches Management